MODAL USAHA DAN PENGETAHUAN KEWIRAUSAHAAN APAKAH MEMPENGARUHI KINERJA UMKM KECAMATAN SYIAH KUALA KOTA BANDA ACEH? - Maulida, Zenitha; Ridha, Ainul; Nurbismi, Nurbismi; Ivana, Farah; Mediyati, Sisca; Masyithah, Syarifah Mauli (Akbis: Media Riset Akuntansi dan Bisnis, 2024)
This study aims to examine whether of influence business capital and entrepreneurial knowledge affect the performance of MSME in Syiah Kuala District, Banda Aceh City.  The research method used is a quantitative. The population of this research is all MSME in Syiah Kuala District, Banda Aceh City, the population of which is 3.706 MSME units. The sampling technique used was purposive sampling and using the Slovin formula, namely 97 MSMEs. The data collection method uses a questionnaire distributed to MSMEs actors. The data analysis techniques used in this research descriptive statistic, multiple linear regression analysis, and hypothesis test both partially (t test) and simultaneously (F test) using SPSS application. The results of the study show that business capital and entrepreneurial knowledge have a positive and significant effect on the performance of MSMEs in Syiah Kuala District, Banda Aceh City, both partially and simultaneously.